Mesoporous carbon-based materials and their applications as non-precious metal electrocatalysts in the oxygen reduction reaction. (20th January 2023) - Collins, Gillian; Kasturi, Palanisamy Rupa; Karthik, Raj; Shim, Jae-Jin; Sukanya, Ramaraj; Breslin, Carmel B.
Abstract: Carbon is truly astonishing and the only element that can form so many different compounds and materials. In recent years, numerous nanostructured carbon-based materials have emerged and within this family, mesoporous and ordered mesoporous carbon have attracted considerable attention. In this paper, we review the recent developments in the applications of mesoporous carbon as an electrocatalyst for the oxygen reduction reaction (ORR). The ORR is one of the most studied electrochemical reactions with applications in the energy and environmental sectors. Following a short introduction to the methodologies employed in the fabrication of mesoporous and ordered mesoporous carbon, the performance of these materials in the ORR is reviewed. Initially, metal free heteroatom doped mesoporous carbon electrocatalysts are described, highlighting the roles of N, S and B as dopants. Next, mesoporous carbon materials with Fe, Co, Mn and Ni, as isolated single atom catalysts, are introduced. The role of mesoporous carbon as a support for nanostructured electrocatalysts is then discussed. Finally, the selectivity of the mesoporous carbon-based electrocatalysts for the four and two-electron ORR is discussed. While further developments and advancements are needed, it is clear that these mesoporous carbon-based materials have the potential to give highly efficient electrocatalysts for both the four and two electron ORR. Indeed, many of the reported electrocatalysts can outperform the commercial Pt/carbon electrocatalysts in alkaline solutions.